1997
DOI: 10.1111/j.1440-1746.1997.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer associated with other primary cancers: A study of 31 patients

Abstract: The aim of this study was to investigate the characteristics of oesophageal cancer associated with other primary cancers and the survival rate after surgery for the patients with these cancers. Of 202 patients with oesophageal cancer treated in the Second Department of Surgery, Shinshu University School of Medicine between 1981 and 1995, 31 patients (15.3%) had oesophageal cancer associated with other primary cancers. Twenty-one synchronous and 10 metachronous associated cancers were found and 25 of them were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…The stages of esophageal cancer among the MPC and NPC cases were distinct, with a higher incidence of stage I disease and a lower incidence of stage IV disease in the MPC group than in the NPC group. Based on the Japanese criteria for staging, 14 stage 0 disease, defined as a tumor invading the mucosa with no lymph node metastasis, was seen more frequently in the patients with MPC than in those with NPC, in accordance with the report of Koide et al 5 Thus, MPC tended to be associated with relatively early stage esophageal cancers. Another primary cancer tended to arise during the early stage of esophageal cancer, and these patients had longer term survival.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The stages of esophageal cancer among the MPC and NPC cases were distinct, with a higher incidence of stage I disease and a lower incidence of stage IV disease in the MPC group than in the NPC group. Based on the Japanese criteria for staging, 14 stage 0 disease, defined as a tumor invading the mucosa with no lymph node metastasis, was seen more frequently in the patients with MPC than in those with NPC, in accordance with the report of Koide et al 5 Thus, MPC tended to be associated with relatively early stage esophageal cancers. Another primary cancer tended to arise during the early stage of esophageal cancer, and these patients had longer term survival.…”
Section: Discussionsupporting
confidence: 81%
“…[1][2][3][4][5][6] Although esophageal cancer is generally accepted to be associated with a poor prognosis, its clinical outcome after surgery is gradually improving. [7][8][9][10] This prompts us to examine the incidence of a second malignant tumor in patients who have had their first tumor successfully treated and complicates the therapeutic strategies for dealing with the second primary cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier studies showed poor prognosis of GTC, especially in tumors that were found at a symptomatic stage, and stressed the importance of early detection of GTC by endoscopic surveillance [8,10,20,29]. Kise et al [7] reported that an increase in the number of screening endoscopic examinations leads to increased early detection of GTC, which suggests that endoscopic surveillance is vital to improving GTC detection.…”
Section: Discussionmentioning
confidence: 99%
“…10 Patients with ESCC frequently develop other primary cancers, such as gastric cancer and head and neck cancer. [11][12][13] In a comprehensive registry of 2,991 patients with ESCC, 18% developed carcinoma in another organ either synchronously or metachronously, with gastric cancer the most frequent followed by head and neck cancer and colorectal cancer. 14 Details of carcinogenesis in patients with multiple primaries that include esophageal carcinoma with other primary carcinoma (ECOPC) remain uncertain.…”
mentioning
confidence: 99%